Common childhood illnesses: a cross-sectional study of commodity stocking patterns and management knowledge among patent and proprietary medicine vendors in Nigeria - Selema Margaret Akuiyibo; Jennifer Anyanti; Babatunde Abiodun Amoo; Dennis Aizobu; Omokhudu Idogho (BMC, 2022)
Abstract Background The trio of commonest illnesses and causes mortality among children under five (Malaria, Pneumonia and Diarrhea) are easily treatable through timely exposure to cost effective interventions at the community level. Patent and proprietary medicine vendors (PPMVs) are a leading source of care for illnesses among under-five children in Nigeria. This study was designed to explore child health services offering, particularly commodity stocking patterns and case management knowledge for common childhood illnesses among PPMVs in Ebonyi and Kaduna States. Methods A descriptive cross-sectional study was conducted among PPMVs in four local government areas across Ebonyi and Kaduna States. Data was collected using semi-structured interviewer-administered questionnaires. Information was obtained on medicine and supplies, knowledge of common childhood illnesses management and referral practices. Results A total of 374 PPMVs were interviewed; the mean age was 33.7 ± 9.8 years. Among the 132 health trained respondents, 59.0% offer treatment services for sick children while 83.5% of the non-health trained respondents offer the same service. At least, 88.0% of the respondents keep stock ACTs, Amoxycilin DT, ORS and Zinc. About 38.5% reported stock-out of ACTs in the month preceding the study, 55.1% reported stock out lasting only 0 to 6 days. Only 83 (22.2%) of respondents knew the correct diagnosis of fast breathing among children aged 2 to less than 12 months old. Education and health training background were associated with a good knowledge of common childhood illnesses management (X2 = 44.88, p < 0.001; X2 = 27.14, p < 0.001). Conclusion The relative constant availability of medicines and commodities for managing childhood illnesses positions PPMVs as a preferred source of care for these illnesses. There is a need to complement steady stock availability with provision of quality services by exposing PPMVs to trainings on integrated community case management of childhood illnesses and implementation of robust supervision mechanism to monitor them.